Understanding community-based forest ecosystem management
Here is a state-of-the-art reference and information source for scientists, community groups and their leaders, resource managers, and ecosystem management practitioners. Healthy ecosystems and community well-being go hand in hand, and the interdependence between the two is the focal point of community-based ecosystem management. The information you'll find in Understanding Community-Based Forest Ecosystem Management will be invaluable in your effort to manage and maintain the ecosystems in your community. Understanding Community-Based Forest Ecosystem Management examines the emergence of community-based ecosystem management (CBEM) in the United States. This comprehensive book blends diverse perspectives, enabling you to draw on the experience and expertise of forest-based practitioners, researchers, and leaders in community-based efforts in the ecosystem management situations that you deal with in your community.